Assessment of in vitro antipsoriatic activity of selected Indian medicinal plants - Singh S.K.; Chouhan H.S.; Sahu A.N.; Narayan G. (My University, 2025)
Context: Phyllanthus simplex Retz. (Phyllanthaceae), Crotolaria juncea Linn. (Leguminosae), Leucas aspera Linn. (Lamiaceae), and Vitex glabrata R.Br. (Verbenaceae) are well-known Indian medicinal plants. Different parts of these plants are used for healing purposes traditionally in the treatment of psoriasis and various other disorders. This prompted us to assess the antipsoriatic activities of these plants. Objectives: Petroleum ether and ethanol extracts of the selected plants, i.e., P. simplex (whole plant), C. juncea (seeds), L. aspera (aerial parts), and V. glabrata (leaves) were investigated for their in vitro antipsoriatic activity. Materials and methods: Antipsoriatic activity of the extracts was evaluated by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay, using HaCaT cells. About 200μl of different concentrations (25, 50, 100, 200, and 400μg/ml) of test samples were prepared in the cell culture medium and incubated for 24h before MTT assay to determine the viable cells. The effect of these extracts on nitric oxide (NO) production and lipid peroxidation was also evaluated. Results: Our findings revealed that these plants showed promising skin keratinocyte antiproliferative activity. However, the petroleum ether extract of C. juncea (CJPE) and ethanol extract of L. aspera (LAEE) were found to exhibit significant activity (IC50 value=45.45 and 55.36μg/ml, respectively). Discussion and conclusions: The inhibitory action against NO production and lipid peroxidation in HaCaT cells suggested that the antipsoriatic activity of the extracts was mediated by an antioxidant mechanism. These findings validate the claims of the use of these plants in the treatment of psoriasis. © 2015 © 2015 Informa Healthcare USA, Inc. All rights reserved: reproduction in whole or part not permitted.